Improved nanocrystal formation, quantum confinement and carrier transport properties of doped Si quantum dot superlattices for third generation photovoltaics. (16th November 2011) - Di, Dawei; Xu, Heli; Perez‐Wurfl, Ivan; Green, Martin A.; Conibeer, Gavin
ABSTRACT An all‐Si tandem solar cell has the potential to achieve high conversion efficiency at low cost. However, the selection and synthesis of candidate material remain challenging. In this work, we show that the conventional 'Si quantum dots (Si QDs) in SiO2 matrix' approach can lead to the formation of over‐sized Si nanocrystals especially when doped with phosphorous, making the size‐dependent quantum confinement less effective. Also, our investigation has shown that the high resistivity of this material has become the performance bottleneck of the solar cell. To resolve these matters, we propose a new design based on Si QDs embedded in a SiO2/Si3N4 hybrid matrix. By replacing the SiO2 tunnel barriers by the Si3N4 layers, the new material manages to constrain the growth of doped Si QDs effectively and enhances the apparent band gap, as shown in X‐ray diffraction, Raman, photoluminescence and optical spectroscopic measurements. Besides, electrical characterisation on Si QD/c‐Si heterointerface test structures indicates the new material possesses improved vertical carrier transport properties. Copyright © 2011 John Wiley & Sons, Ltd.